Behcet's Disease With Cerebral Artery Infarction Caused by Cerebral Arteritis as an Early Symptom Only With Elevated Interleukin-8 - Yin, Hao; Song, Yun; Zheng, Meimei; Han, Ju; Tang, Jiyou (Frontiers in Neurology, 2019)
Background: Behcet's disease (BD) is multi-systemic vasculitis, which generally is repeated oral and genital ulcerations as well as ocular and skin lesions. Today, the pathogenesis of BD remains mostly unknown. It is also suggested that the disease is probably related to autoinflammatory and autoimmune disorders, and innate immunity damages were perceived as key in its pathologic process. Only 5% of BD patients have neurological involvement, and it usually occurs in 4–6 years after the initial symptoms. Early onset of neurological impairment makes it difficult to diagnose and treat definitely. Case Presentation: A 38-year-old man was admitted to our hospital with numbness and weakness of the left extremities. Diffusion magnetic resonance imaging (MRI) revealed focal infarction in the posterior limb of the internal capsule. Skin pathology suggested small vessel vasculitis, and high-resolution MRI revealed intracranial arteritis. The patient had a negative skin pathery test and then developed a scar at the venous puncture site at the early stage of disease. Laboratory examination showed that interleukin 8 (IL-8) increased. The patient was treated with an immunosuppressive agent including mycophenolate mofetil, hydroxychloroquine, and colchicine. All symptoms were alleviated after half a year's treatment. There was neither stroke nor recurrence of oral ulcer thereafter. Conclusion: This case demonstrates that neurological involvement might be an early symptom of BD. IL-8 could act as a novel target for the treatment of BD theoretically and probably play a key role in disease recovery.